Analysis of the Effectiveness of Implementation of Inclusion Education Program at Lebak Bulus 2 Primary School, South Jakarta - Hayun, Muhammad; Sari, Pratiwi Kartika; Lubis, Maesaroh (IJBLE Scientific Publications Community Inc., 2024)
Inclusive Education was born as a response to increasingly exclusive educational needs. Inclusive education is an educational program that aims to provide opportunities for all students, both normal and those with physical, mental, emotional, intellectual, and social and economic disabilities (ABK) to learn together in one class and school without discrimination or treatment. bullying. The aim of this research is to provide recommendations and information to stakeholders of the inclusive education program regarding the process of successful implementation of the program in the field, as well as developing social competency modules and social competency instruments to be used as teaching materials in inclusive schools. This research uses qualitative research with a case study approach. The case study research focuses on case studies regarding inclusive education at SDN Lebak Bulus 02 Pagi. Data collection used in this research was interviews, observation and documentation. The results of this research obtained information that; The implementation of the inclusion program at SDN Lebak Bulus 02 is still experiencing obstacles, especially special educators or special assistant teachers (GPK) who are not yet available, in addition to that, supporting facilities for children with special needs are not yet available optimally, thus hampering the learning process for students with special needs.